Energy absorption in lattice structures in dynamics: Experiments. (March 2016) - Ozdemir, Zuhal; Hernandez-Nava, Everth; Tyas, Andrew; Warren, James A.; Fay, Stephen D.; Goodall, Russell; Todd, Iain; Askes, Harm
Highlights: Experimental study. Static and dynamic behaviour of micro-truss materials. Prediction of strain-rate sensitivity. Abstract: Lattice structures offer the potential to relatively easily engineer specific (meso-scale properties (cell level)), to produce desirable macro-scale material properties for a wide variety of engineering applications including wave filters, blast and impact protection systems, thermal insulation, structural aircraft and vehicle components, and body implants. The work presented here focuses on characterising the quasi-static and, in particular, the dynamic load-deformation behaviour of lattice samples. First, cubic, diamond and re-entrant cube lattice structures were tested under quasi-static conditions to investigate failure process and stress–strain response of such materials. Following the quasi-static tests, Hopkinson pressure bar (HPB) tests were carried out to evaluate the impact response of these materials under high deformation rates. The HPB tests show that the lattice structures are able to spread impact loading in time and to reduce the peak impact stress. A significant rate dependency of load-deformation characteristics was identified. This is believed to be the first published results of experimental load-deformation studies of additively manufactured lattice structures. The cubic and diamond lattices are, by a small margin, the most effective of those lattices investigated to achieve this.